Pengaruh Good Corporate Governace dan Profitabilitas terhadap Nilai Perusahaan (Studi Kasus pada Perusahaan Sektor Industri Semen yang Terdaftar di Bursa Efek Indonesia Tahun 2016-2019) - Yogi Maulana; Maryani Nur (Program Studi Magister Manajemen Universitas Krisnadwipayana, 2022)
This research is aims to examine and analyze the effect of good corporate governance and profitability on firm value. Case studies of cement industrial sector companies listed on the Indonesia Stock Exchange in 2016–2019. Hypothesis testing uses Moderated Regression Analysis. The results of this study indicate that GCG with indicators of institutional ownership, audit committee, and partially independent commissioners has no significant effect on firm value, while GCG with indicators of public ownership and directors partially has a significant effect on firm value, profitability partially has a significant effect on firm value and profitability can moderate (strengthen) the effect of GCG on firm value